Economic benefits of the Mediterranean-style diet consumption in Canada and the United States - Mohammad M.H. Abdullah; Jason P.H. Jones; Peter J.H. Jones (Food & Nutrition Research, 2015)
Background: The Mediterranean-style diet (MedDiet) is an established healthy-eating behavior that has consistently been shown to favorably impact cardiovascular health, thus likely improving quality of life and reducing costs associated with cardiovascular disease (CVD). Data on the economic benefits of MedDiet intakes are, however, scarce. Objective: The objective of this study was to estimate the annual healthcare and societal cost savings that would accrue to the Canadian and American public, independently, as a result of a reduction in the incidence of CVD following adherence to a MedDiet. Design: A variation in cost-of-illness analysis entailing three stages of estimations was developed to 1) identify the proportion of individuals who are likely to adopt a MedDiet in North America, 2) assess the impact of the MedDiet intake on CVD incidence reduction, and 3) impute the potential savings in costs associated with healthcare and productivity following the estimated CVD reduction. To account for the uncertainty factor, a sensitivity analysis of four scenarios, including ideal, optimistic, pessimistic, and very-pessimistic assumptions, was implemented within each of these stages. Results: Significant improvements in CVD-related costs were evident with varying MedDiet adoption and CVD reduction rates. Specifically, CAD $41.9 million to 2.5 billion in Canada and US $1.0–62.8 billion in the United States were estimated to accrue as total annual savings in economic costs, given the ‘very-pessimistic’ through ‘ideal’ scenarios. Conclusions: Closer adherence to dietary behaviors that are consistent with the principles of the MedDiet is expected to contribute to a reduction in the monetary burdens of CVD in Canada, the United States, and possibly other parts of the world.